Preparation method of recrystallized silicon carbide-silicon carbonitride ceramic membrane
By applying a propargyl polysilazane solution to a porous substrate and subjecting it to multiple pyrolysis and recrystallization processes, a recrystallized silicon carbide-silicon carbonitride ceramic membrane with high rejection rate and high temperature stability was prepared. This solved the problem of low rejection rate in existing nanofiltration membranes and achieved improved precision and corrosion resistance.
Patent Information
- Application Number
- CN202511468420.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-10-15
AI Technical Summary
Existing nanofiltration membrane preparation methods result in low ceramic membrane rejection rates, and inorganic nanofiltration membranes exhibit poor dispersibility in oil-based or water-based coatings, making it difficult to improve filtration accuracy and corrosion resistance.
A porous substrate was impregnated and stretched in a solution containing propargyl polysilazane, and then subjected to multiple pyrolysis and recrystallization processes to prepare a recrystallized silicon carbide-silicon carbonitride ceramic film. By controlling the pyrolysis and recrystallization processes, a high-temperature stable SiC-SiCN ceramic film was formed.
The prepared recrystallized silicon carbide-silicon carbonitride ceramic membrane has a filtration accuracy of ≤1nm, high rejection rate and excellent high temperature resistance, and is suitable for separation and protection applications in extreme environments.
Smart Images

Figure CN120939767A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofiltration technology, and in particular to a method for preparing a recrystallized silicon carbide-silicon carbonitride ceramic membrane. Background Technology
[0002] Membrane filtration precision is categorized into ultrafiltration membranes, nanofiltration membranes, and reverse osmosis membranes. Existing nanofiltration membranes are generally classified into organic and inorganic materials. Inorganic nanofiltration membranes are widely used due to their excellent corrosion resistance and high strength. The materials used for inorganic nanofiltration membranes are typically ceramic membranes such as silicon carbide (SiC), alumina (Al2O3), zirconium oxide (ZrO2), titanium oxide (TiO2), silicon oxide (SiO2), and silicon nitride.
[0003] Currently, the general method for preparing silicon nitride ceramic membranes is to prepare coatings using inorganic materials such as silicon particles or silicon nitride powder, and then sinter them. However, since silicon particles and silicon nitride powders have poor dispersibility in both oil-based and water-based coatings, the resulting ceramic membranes have low retention rates, which need to be further improved. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a method for preparing a recrystallized silicon carbide-silicon carbonitride ceramic membrane. The recrystallized silicon carbide-silicon carbonitride ceramic membrane prepared by the method provided by this invention has a filtration accuracy of ≤1nm, a high rejection rate, and excellent high-temperature resistance.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a recrystallized silicon carbide-silicon carbonitride ceramic film, comprising the following steps: After the first application of a polysilazane solution onto a porous matrix, a first pyrolysis is performed to obtain a pyrolytic material. A second pyrolysis was performed after a second application of a polysilazane solution onto the pyrolysis material to obtain the recrystallized silicon carbide-silicon carbonitride ceramic film. The first pyrolysis process is as follows: The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first heat preservation. The temperature is increased from 300℃ to 600℃ at a rate of 2~5℃ / min for the second heat preservation. The temperature is increased from 600℃ to 1000℃ at a rate of 3~5℃ / min for the third heat preservation. The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min for the fourth heat preservation. Repeat the process of first pyrolysis after first applying polysilazane solution to the porous matrix until the pore size of the pyrolysis material is less than or equal to 1 nm. The second pyrolysis includes sequentially performing a first pyrolysis and recrystallization; The recrystallization process is as follows: The temperature was increased from 1200℃ to 1400℃ at a rate of 2℃ / min for the fifth heat preservation. The temperature was increased from 1400℃ to 1600℃ at a rate of 2~5℃ / min for the sixth heat preservation. The recrystallization is carried out under a nitrogen atmosphere or an ammonia atmosphere; The polysilazane solution is a solution containing propargyl polysilazane or an organopolysilazane Durrazane 1500 Rapid Cure fast-drying resin. The propargyl polysilazane contains 10-30 mol of propargyl groups.
[0006] Preferably, the first heat preservation time is 1-2 hours, the second heat preservation time is 2 hours, the third heat preservation time is 2 hours, the fourth heat preservation time is 1-2 hours, the fifth heat preservation time is 1 hour, and the sixth heat preservation time is 2 hours.
[0007] Preferably, the preparation method of the propargyl polysilazane includes the following steps: After mixing polysilazane oligomer, triethylamine and toluene, bromopropyne was added dropwise to the resulting mixture to carry out a condensation reaction, thereby obtaining the propargyl polysilazane.
[0008] Preferably, the average molecular weight of the polysilazane oligomer is 900-1000, the molar ratio of the polysilazane oligomer to triethylamine is 3:0.8-1.2, and the molar ratio of the polysilazane oligomer to bromopropyne is 9:0.8-1.2; the condensation reaction is carried out at a temperature of 60°C for 5 hours.
[0009] Preferably, the concentration of the solution containing propargyl polysilazane is 10-30 wt%, and the solvent includes one or more of ethyl acetate, toluene, and acetone; The first and second applications are performed by immersion lifting; the immersion lifting speed is 0.1~10mm / s.
[0010] Preferably, the porous substrate includes a support and a microfiltration membrane and an ultrafiltration membrane sequentially located on the support; the microfiltration membrane has a pore size of 0.5~1μm and a thickness of 40~60μm; the ultrafiltration membrane has a pore size of 20~50nm and a thickness of 30~50μm.
[0011] Preferably, the method for preparing the porous matrix includes the following steps: Silicon carbide, cellulose, dextran, vegetable oil, water and glycerol are mixed and then kneaded, extruded, degummed and sintered in sequence to obtain a support. A microfiltration coating is applied to the support, and a second sintering is performed to obtain a microfiltration body with a support-microfiltration membrane. An ultrafiltration coating is applied to the microfiltration membrane of the microfiltration body, and a third sintering is performed to obtain the porous matrix.
[0012] Preferably, the silicon carbide, cellulose, dextran, vegetable oil, water, and glycerol constitute the support material; the mass percentage of each component in the support material is 70% silicon carbide, 6% cellulose, 3% dextran, 1% vegetable oil, 19% water, and 1% glycerol. The kneading time is 3-5 hours; the degumming temperature is 140-160℃ and the time is 8-12 hours. The first sintering process is as follows: The temperature is increased from room temperature by 1-2℃ to 590-610℃ and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1.5~2.5 hours. The temperature is increased from 2190~2210℃ to 2440~2460℃ at a rate of 3~5℃ / min and held for 1~3 hours. After the first sintering, the process further includes cooling to room temperature, wherein the cooling rate is 2~5℃ / min.
[0013] Preferably, the microfiltration coating comprises the following components by weight percentage: The composition includes 60% silicon carbide powder, 10% vegetable oil, 25% water, and 5% glycerol; the particle size of the silicon carbide powder is 7 μm. The second sintering process is as follows: The temperature is increased from room temperature to 590-610℃ at a rate of 1-2℃ / min and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1~3 hours. After the second sintering, the process further includes cooling to room temperature at a rate of 2-5°C / min.
[0014] Preferably, the ultrafiltration coating comprises the following components by mass percentage: The composition includes 60% silicon carbide powder, 10% vegetable oil, 25% water, and 5% glycerol; the particle size of the silicon carbide powder is 0.5 μm. The third sintering process is as follows: The temperature is increased from room temperature to 590-610℃ at a rate of 1-2℃ / min and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature was increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 0.5~1.5h. After the third sintering, the process further includes cooling to room temperature at a rate of 2-5°C / min.
[0015] This invention provides a method for preparing recrystallized silicon carbide-silicon carbonitride ceramic films.
[0016] 1. Compared with existing recrystallized silicon carbide ceramic membranes, the present invention uses a porous substrate to be impregnated and pulled in a solution containing propargyl polysilazane (PPSZ), and then formed into a film through a first pyrolysis and a second pyrolysis. The film layer has better immersion and tighter bonding.
[0017] 2. This invention uses a solution containing propargyl polysilazane or organopolysilazane Durazane 1500 RapidCure fast-drying resin as a precursor to prepare ceramic membranes, which have high ceramic yield, excellent high temperature stability, high rejection rate and controllable microstructure, and are suitable for separation and protection applications in extreme environments.
[0018] 3. Compared with the existing recrystallized silicon carbide ceramic membrane with a filtration accuracy of ≥0.05μm, the initial membrane pore size of the porous substrate can reach 20~50nm. Through the first pyrolysis, the pores are filled to increase the pore size to below 1nm.
[0019] 4. During the second pyrolysis process, the pyrolysis material is sintered at a high temperature of 1400℃, and neck bonding is achieved by atomic diffusion on the surface of silicon carbonitride (SiCN) particles, thus realizing an amorphous / crystalline state. That is, a fully recrystallized silicon carbide (SiC)-silicon carbonitride (SiCN) ceramic film is prepared. Attached Figure Description
[0020] Figure 1 The flowchart illustrates the preparation method of the recrystallized silicon carbide-silicon carbonitride ceramic film provided by this invention. Detailed Implementation
[0021] Figure 1 The following is a flowchart of the preparation method of recrystallized silicon carbide-silicon carbonitride ceramic film provided by the present invention, in conjunction with... Figure 1 The preparation method of the present invention will be described in detail.
[0022] This invention provides a method for preparing a recrystallized silicon carbide-silicon carbonitride ceramic film, comprising the following steps: After the first application of a polysilazane solution onto a porous matrix, a first pyrolysis is performed to obtain a pyrolytic material. A second pyrolysis was performed after a second application of a polysilazane solution onto the pyrolysis material to obtain the recrystallized silicon carbide-silicon carbonitride ceramic film. The first pyrolysis process is as follows: The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first heat preservation. The temperature is increased from 300℃ to 600℃ at a rate of 2~5℃ / min for the second heat preservation. The temperature is increased from 600℃ to 1000℃ at a rate of 3~5℃ / min for the third heat preservation. The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min for the fourth heat preservation. Repeat the process of applying a polysilazane solution to a porous substrate and then performing the first pyrolysis until the pore size of the pyrolysis material is less than or equal to 1 nm. The second pyrolysis includes sequentially performing a first pyrolysis and recrystallization; The recrystallization process is as follows: The temperature was increased from 1200℃ to 1400℃ at a rate of 2℃ / min for the fifth heat preservation. The temperature was increased from 1400℃ to 1600℃ at a rate of 2~5℃ / min for the sixth heat preservation. The recrystallization is carried out under a nitrogen atmosphere or an ammonia atmosphere; The polysilazane solution is a solution containing propargyl polysilazane or an organopolysilazane Durrazane 1500 Rapid Cure fast-drying resin. The propargyl polysilazane contains 10-30 mol of propargyl groups.
[0023] Unless otherwise specified, the raw materials used in this invention are preferably commercially available products.
[0024] In this invention, a polysilazane solution is first applied to a porous matrix, followed by a first pyrolysis to obtain a pyrolytic material.
[0025] In this invention, the porous substrate preferably comprises a support and a microfiltration membrane and an ultrafiltration membrane sequentially located on the support. In this invention, the microfiltration membrane preferably has a pore size of 0.5~1μm, is preferably made of silicon carbide, and has a thickness of 40~60μm. In this invention, the ultrafiltration membrane preferably has a pore size of 20~50nm, is preferably made of silicon carbide, and has a thickness of 30~50μm.
[0026] In this invention, the method for preparing the porous matrix preferably includes the following steps: Silicon carbide, cellulose, dextran, vegetable oil, water and glycerol are mixed and then kneaded, extruded, degummed and sintered in sequence to obtain a support. A microfiltration coating is applied to the support, and a second sintering is performed to obtain a microfiltration body with a support-microfiltration membrane. An ultrafiltration coating is applied to the microfiltration membrane of the microfiltration body, and a third sintering is performed to obtain the porous matrix.
[0027] This invention involves mixing silicon carbide, cellulose, dextran, vegetable oil, water, and glycerol, and sequentially performing kneading, extrusion, degumming, and a first sintering process to obtain a support. In this invention, the silicon carbide, cellulose, dextran, vegetable oil, water, and glycerol constitute the support raw material; the mass percentage of each component in the support raw material is 70% silicon carbide, 6% cellulose, 3% dextran, 1% vegetable oil, 19% water, and 1% glycerol. In this invention, the kneading time is preferably 3-5 hours, specifically 3 hours, 4 hours, or 5 hours. In this invention, the degumming temperature is preferably 140-160°C, specifically 140°C, 150°C, or 160°C; the degumming time is preferably 8-12 hours, specifically 8 hours, 10 hours, or 12 hours.
[0028] In this invention, the first sintering process is preferably as follows: The temperature is increased from room temperature by 1-2℃ to 590-610℃ and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1.5~2.5 hours. The temperature is increased from 2190~2210℃ to 2440~2460℃ at a rate of 3~5℃ / min and held for 1~3 hours. The first sintering process is further preferably: The temperature was increased from room temperature by 1-2℃ to 600℃ and held for 1 hour. The temperature was increased from 600℃ to 1600℃ at a rate of 5~10℃ / min and held for 1 hour. The temperature was increased from 1600℃ to 2200℃ at a rate of 3~5℃ / min and held for 2 hours. The temperature was increased from 2200℃ to 2450℃ at a rate of 3~5℃ / min and held for 1 hour.
[0029] In this invention, the temperature is raised from room temperature to 590-610°C at a rate of 1-2°C and held for 0.5-1.5 hours. This process removes the binder (dextran and glycerol) and solvent. The first heating rate is preferably controlled at 1-2°C / min to prevent the film from cracking.
[0030] In this invention, the temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h; this process can activate the particle surface.
[0031] In this invention, the temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1.5~2.5h; during this process, the SiC surface evaporates and condenses, a neck is formed, and oxidation is prevented.
[0032] In this invention, the temperature is increased from 2190~2210℃ to 2440~2460℃ at a rate of 3~5℃ / min and held for 1~3 hours. This process can achieve densification and promote grain growth, so that the grain size is within a suitable range and the strength is improved.
[0033] After the first sintering, the present invention preferably further includes cooling to room temperature, wherein the cooling rate is preferably 2~5°C / min. In the present invention, this process can prevent thermal stress cracking.
[0034] In this invention, the first sintering is preferably carried out under a vacuum or protective atmosphere, wherein the protective atmosphere is preferably argon.
[0035] In this invention, the aperture of the support is preferably 5~10μm.
[0036] After obtaining the support, the present invention applies a microfiltration coating to the support and performs a second sintering to obtain a microfiltration body having a support-microfiltration membrane. In the present invention, the microfiltration coating preferably comprises the following components in mass percentage: 60% silicon carbide powder, 10% vegetable oil, 25% water and 5% glycerol; the particle size of the silicon carbide powder is 7 μm.
[0037] In this invention, the second sintering process is preferably as follows: The temperature is increased from room temperature to 590-610℃ at a rate of 1-2℃ / min and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1~3 hours. The second sintering process is further preferably: The temperature was increased from room temperature to 600℃ at a rate of 1~2℃ / min and held for 1 hour. The temperature was increased from 600℃ to 1600℃ at a rate of 5~10℃ / min and held for 1 hour. Increase the temperature from 1600℃ to 2200℃ at a rate of 3~5℃ / min and hold for 1~3 hours.
[0038] In this invention, the temperature is increased from room temperature to 590-610°C at a rate of 1-2°C / min and held for 0.5-1.5 hours. This process can remove the binder / solvent and prevent the film from cracking.
[0039] In this invention, the temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h, which can activate the particle surface.
[0040] In this invention, the temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1~3h. This process can promote grain growth and form a dense film.
[0041] After the second sintering, the present invention preferably further includes cooling to room temperature, wherein the cooling rate is preferably 2~5°C / min. In the present invention, this process can prevent thermal stress cracking.
[0042] In this invention, the second sintering is preferably carried out under a vacuum or protective atmosphere, preferably argon.
[0043] After obtaining a microfiltration body with a support-microfiltration membrane, the present invention applies an ultrafiltration coating to the microfiltration membrane of the microfiltration body and performs a third sintering to obtain the porous matrix. In the present invention, the ultrafiltration coating preferably comprises the following components in mass percentage: 60% silicon carbide powder, 10% vegetable oil, 25% water and 5% glycerol; the particle size of the silicon carbide powder is 0.5 μm.
[0044] In this invention, the third sintering process is preferably as follows: The temperature is increased from room temperature to 590-610℃ at a rate of 1-2℃ / min and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature was increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 0.5~1.5h. The third sintering process is further preferably: The temperature was increased from room temperature to 600℃ at a rate of 1~2℃ / min and held for 1 hour. The temperature was increased from 600℃ to 1600℃ at a rate of 5~10℃ / min and held for 1 hour. The temperature is increased from 1600℃ to 2200℃ at a rate of 3~5℃ / min and held for 0.5~1.5h.
[0045] In this invention, the temperature is increased from room temperature to 590-610°C at a rate of 1-2°C / min and held for 0.5-1.5 hours. This process can remove the binder / solvent and prevent the film from cracking.
[0046] In this invention, the temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h, which can activate the particle surface.
[0047] In this invention, the temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 0.5~1.5h. During this process, grain growth can be promoted to form a dense film layer.
[0048] After the third sintering, the present invention further includes cooling to room temperature, wherein the cooling rate is preferably 2~5℃ / min.
[0049] In this invention, the third sintering is preferably carried out under a vacuum or protective atmosphere, preferably argon.
[0050] In this invention, the propargyl content in the propargyl polysilazane is 10-30 mol%, preferably 10 mol%, 15 mol%, 20 mol%, 25 mol%, or 30 mol%. In this invention, if the propargyl content in the propargyl polysilazane is too low (<10 mol%), it will lead to insufficient crosslinking and a decrease in ceramic yield; if it is too high (>30 mol%), it will lead to violent gas release during pyrolysis and cracking of the film layer.
[0051] In this invention, the polysilazane solution is a solution containing propargyl polysilazane or an organopolysilazane Durazane 1500 rapid cure resin. Preferably, the organopolysilazane Durazane 1500 rapid cure resin is purchased from Merck, Germany.
[0052] In this invention, the concentration of the solution containing propargyl polysilazane is preferably 10-30 wt%, specifically preferably 10 wt%, 15 wt%, 20 wt%, 25 wt%, or 30 wt%. In this invention, the solvent of the solution containing propargyl polysilazane preferably includes one or more of ethyl acetate, toluene, and acetone.
[0053] In this invention, the preparation method of the propargyl polysilazane preferably includes the following steps: A polysilazane oligomer, triethylamine, and toluene are mixed, and then bromopropyne is added dropwise to the resulting mixture to induce a condensation reaction, yielding the propargyl polysilazane. In this invention, the average molecular weight of the polysilazane oligomer is preferably 900-1000. In this invention, the molar ratio of the polysilazane oligomer to triethylamine is preferably 3:0.8-1.2, specifically preferably 3:0.8, 3:0.9, 3:1, 3:1.1, or 3:1.2. In this invention, the molar ratio of the polysilazane oligomer to bromopropyne is preferably 9:0.8-1.2, specifically preferably 9:0.8, 9:0.9, 9:1, 9:1.1, or 9:1.2. In this invention, the mixing temperature of the polysilazane oligomer, triethylamine, and toluene is preferably 60°C, and the mixing of the polysilazane oligomer, triethylamine, and toluene is preferably carried out under stirring conditions. In this invention, the bromopropyne is preferably added dropwise over 120 minutes. In this invention, the condensation reaction temperature is preferably 60°C, and the time is preferably 5 hours; the condensation reaction is preferably carried out under stirring. After the condensation reaction, this invention preferably further includes: after the obtained condensation reaction system has cooled to room temperature, centrifuging the cooled condensation reaction system to obtain a yellowish-brown transparent clear liquid; washing the yellowish-brown transparent clear liquid with toluene and recovering the washing liquid; distilling the washing liquid under vacuum to remove the solvent, obtaining a dark brown transparent viscous resin, i.e., the propyne-based polysilazane. In this invention, the washing is preferably performed twice.
[0054] In this invention, the first application is preferably performed by dip-lifting, and the dip-lifting speed is preferably 0.1~10 mm / s, specifically preferably 0.1 mm / s, 0.5 mm / s, 1 mm / s, 1.5 mm / s, 2 mm / s, 2.5 mm / s, 3 mm / s, 3.5 mm / s, 4 mm / s, 4.5 mm / s, 5 mm / s, 5.5 mm / s, 6 mm / s, 6.5 mm / s, 7 mm / s, 7.5 mm / s, 8 mm / s, 8.5 mm / s, 9 mm / s, 9.5 mm / s, or 10 mm / s. After the first application, the invention preferably includes curing, and the curing temperature is preferably 40°C, and the curing time is preferably 1 hour.
[0055] In this invention, the first pyrolysis process is as follows: The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first heat preservation. The temperature is increased from 300℃ to 600℃ at a rate of 2~5℃ / min for the second heat preservation. The temperature is increased from 600℃ to 1000℃ at a rate of 3~5℃ / min for the third heat preservation. The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min for the fourth heat preservation.
[0056] In this invention, the first pyrolysis is preferably carried out under a protective atmosphere, which is preferably argon.
[0057] After the first pyrolysis, the present invention preferably further includes furnace cooling to room temperature.
[0058] In this invention, the first heat preservation time is preferably 1-2 hours. During the first heat preservation process, which involves heating from room temperature to 300°C at a rate of 1-2°C / min, the solvent evaporates, and the residual propargyl groups further crosslink.
[0059] In this invention, the second heat preservation time is preferably 2 hours. In this invention, during the second heat preservation process of heating from 300°C to 600°C at a rate of 2~5°C / min, the side chains decompose (releasing C2H2 and H2) to form a Si-N network.
[0060] In this invention, the third heat preservation time is preferably 2 hours. During the third heat preservation process, which involves heating from 600°C to 1000°C at a rate of 3-5°C / min, amorphous SiCN (β-SiCN) is generated, releasing NH3.
[0061] In this invention, the fourth heat preservation time is preferably 1 to 2 hours. In this invention, during the fourth heat preservation process of heating from 1000°C to 1200°C at a rate of 2°C / min, preliminary crystallization (nano-β-SiC / Si3N4) occurs.
[0062] Repeat the process of first applying the polysilazane solution to the porous substrate and then performing the first pyrolysis until the pore size of the pyrolysis material is less than or equal to 1 nm.
[0063] After obtaining the pyrolysis material, the present invention applies a polysilazane solution to the pyrolysis material for a second time and then performs a second pyrolysis to obtain the recrystallized silicon carbide-silicon carbonitride ceramic film.
[0064] In this invention, the method and parameters of the second application are the same as those in the above-described technical solution and will not be repeated here. In this invention, the parameters of the polysilazane solution are the same as those in the above-described technical solution and will not be repeated here.
[0065] In this invention, the second pyrolysis includes sequentially performing a first pyrolysis and recrystallization; The recrystallization process is as follows: The temperature was increased from 1200℃ to 1400℃ at a rate of 2℃ / min for the fifth heat preservation. The temperature was increased from 1400℃ to 1600℃ at a rate of 2~5℃ / min for the sixth heat preservation.
[0066] In this invention, the recrystallization is preferably carried out under a nitrogen atmosphere or an ammonia (NH3) atmosphere, more preferably under a nitrogen atmosphere. In this invention, the flow rate of the nitrogen or ammonia atmosphere is independently preferably 50-100 mL / min, specifically preferably 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, or 100 mL / min. In this invention, pyrolysis under a nitrogen or ammonia atmosphere can suppress the formation of free carbon and increase the N content (increase the Si3N4 phase).
[0067] In this invention, the fifth heat preservation time is preferably 1 hour.
[0068] In this invention, the sixth heat preservation time is preferably 2 hours.
[0069] In this invention, during recrystallization, the phase evolution is: β-SiCN → α-SiC (1-3 nm) + Si3N4 (amorphous / crystalline). Free carbon may form a graphene-like structure (depending on the precursor C / N ratio). Densification mechanism: Evaporation-condensation and diffusion work together, reducing porosity to <40%.
[0070] In this invention, the second pyrolysis process specifically includes: The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first heat preservation. The temperature is increased from 300℃ to 600℃ at a rate of 2~5℃ / min for the second heat preservation. The temperature is increased from 600℃ to 1000℃ at a rate of 3~5℃ / min for the third heat preservation. The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min for the fourth heat preservation. The temperature was increased from 1200℃ to 1400℃ at a rate of 2℃ / min for the fifth heat preservation. The temperature was increased from 1400℃ to 1600℃ at a rate of 2~5℃ / min for the sixth heat preservation.
[0071] After the second pyrolysis, the present invention preferably cools the furnace to room temperature.
[0072] In this invention, during the first and second pyrolysis processes, when the temperature reaches above 600°C, the temperature needs to be increased slowly (<3°C / min) to avoid rapid gas release that could cause the membrane to rupture.
[0073] In this invention, the propargyl crosslinking in propargyl polysilazane can suppress mass loss and increase the ceramic membrane yield to 60-80%. At the same time, it also gives the obtained ceramic membrane excellent high-temperature stability and controllable microstructure, making it suitable for separation and protection applications in extreme environments.
[0074] In this invention, the recrystallized silicon carbide-silicon carbonitride ceramic membrane can be used for nanofiltration of liquids.
[0075] The following detailed description of the preparation method of recrystallized silicon carbide-silicon carbonitride ceramic film provided by the present invention, with reference to the embodiments, should not be construed as limiting the scope of protection of the present invention.
[0076] Example 1 The preparation method of recrystallized silicon carbide-silicon carbonitride ceramic film includes the following steps: Step 1, Preparation of the support: The raw materials are mixed according to the following mass percentages: 70% silicon carbide, 6% cellulose, 3% dextran, 1% vegetable oil (specifically rice bran oil), 19% water and 1% glycerol. The mixture is then subjected to kneading (room temperature, 4h), extrusion, degumming (150℃, 10h) and first sintering. The mixture is cooled to room temperature at a cooling rate of 2~5℃ / min to obtain the support. The filter pore size of the obtained support is 10μm.
[0077] The first sintering process is as follows: The temperature was increased from room temperature to 600℃ at a rate of 1~2℃ / min and held for 1 hour. The temperature was increased from 600℃ to 1600℃ at a rate of 5~10℃ / min and held for 1 hour. The temperature was increased from 1600℃ to 2200℃ at a rate of 3~5℃ / min and held for 2 hours. Heat from 2200℃ to 2450℃ at a rate of 3~5℃ / min and hold for 3 hours; The first sintering is carried out in argon gas.
[0078] Step 2: Preparation of microfiltration membrane with support: Silicon carbide powder (7μm particle size), vegetable oil, water and glycerol were mixed in a mass ratio of 60:10:25:5 to obtain a microfiltration coating.
[0079] The microfiltration coating is applied to the support and then sintered a second time to obtain a microfiltration membrane with a pore size of 1 μm and a thickness of 40~60 μm.
[0080] The second sintering process is as follows: The temperature was increased from room temperature to 600℃ at a rate of 1~2℃ / min and held for 1 hour. The temperature was increased from 600℃ to 1600℃ at a rate of 5~10℃ / min and held for 1 hour. The temperature was increased from 1600℃ to 2200℃ at a rate of 3~5℃ / min and held for 2 hours. The temperature was reduced from 2200℃ to room temperature at a cooling rate of 2~5℃ / min; The second sintering is carried out in argon gas.
[0081] Step 3: Preparation of a porous matrix with a support-microfiltration membrane-ultrafiltration membrane: Silicon carbide powder (particle size 0.5μm), vegetable oil, water and glycerol were mixed in a mass ratio of 60:10:25:5 to obtain an ultrafiltration coating. The ultrafiltration coating was coated onto the microfiltration membrane and then subjected to a third sintering process to obtain a porous matrix with a pore size of 50 nm. The thickness of the ultrafiltration membrane was 30~50 μm. The third sintering process is as follows: The temperature was increased from room temperature to 600℃ at a rate of 1~2℃ / min and held for 1 hour. The temperature was increased from 600℃ to 1600℃ at a rate of 5~10℃ / min and held for 1 hour. The temperature was increased from 1600℃ to 2200℃ at a rate of 3~5℃ / min and held for 1 hour. The temperature was reduced from 2200℃ to room temperature at a cooling rate of 2~5℃ / min; The third sintering is carried out in argon gas.
[0082] Step 4: After applying a solution containing propargyl polysilazane, perform the first pyrolysis: ① Preparation of propargyl polysilazane: Polysilazane oligomer (LSZ, average molecular weight 900-1000), triethylamine, and toluene were placed in a flask, stirred, and heated to 60°C. Bromopropyne was added dropwise over approximately 120 minutes, and the reaction was continued with stirring for 5 hours, resulting in the formation of a large amount of white salt. After cooling, the solution was centrifuged to obtain a yellowish-brown transparent clear liquid. The salt was washed with toluene, and the washing liquid was recovered (washed twice). The solvent was removed by distillation under vacuum to obtain a dark brown transparent viscous resin PPSZ. The molar ratio of polysilazane oligomer to triethylamine was 3:1, and the molar ratio of polysilazane oligomer to bromopropyne was 9:1. The propargyl content in the obtained propargyl polysilazane was 30 mol%.
[0083] ② Dissolve propargyl polysilazane in ethyl acetate to form a 30wt% solution containing propargyl polysilazane.
[0084] ③ A solution containing propargyl polysilazane was coated on a porous substrate using the dip-coating method. The dip-coating speed was 10 mm / s. After coating, the substrate was cured at 40°C for 1 hour and then subjected to the first pyrolysis. The first pyrolysis process is as follows: The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first holding time of 1h (argon atmosphere). The temperature was increased from 300℃ to 600℃ at a rate of 2~5℃ / min for a second holding time of 2h (argon atmosphere); The temperature was increased from 600℃ to 1000℃ at a rate of 3~5℃ / min, and a third holding time of 2h was performed (argon atmosphere). The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min, and then held for 2 hours (argon atmosphere). The furnace temperature was lowered from 1200℃ to room temperature. Repeat step ③2 times to obtain the pyrolytic material.
[0085] Step 5: After applying a solution containing propargyl polysilazane, a second pyrolysis is performed. A solution containing propargyl polysilazane was coated onto the pyrolytic material using the dip-coating method at a speed of 10 mm / s. After coating, the material was cured at 40°C for 1 hour, followed by a second pyrolysis.
[0086] The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first holding time of 1h (argon atmosphere). The temperature was increased from 300℃ to 600℃ at a rate of 2~5℃ / min for a second holding time of 2h (argon atmosphere); The temperature was increased from 600℃ to 1000℃ at a rate of 3~5℃ / min, and a third holding time of 2h was performed (argon atmosphere). The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min, and then held for 2 hours (argon atmosphere). The temperature was increased from 1200℃ to 1400℃ at a rate of 2℃ / min, and then held for 1 hour (in a nitrogen atmosphere). The temperature was increased from 1400℃ to 1600℃ at a rate of 2~5℃ / min, and then held for 2 hours in a nitrogen atmosphere. Cool to room temperature in the furnace to obtain the product.
[0087] Performance Characterization The gas permeability of the obtained ceramic membrane was determined according to GB / T 1969-1996 "Test Method for Permeability of Porous Ceramics". The result was: He flux was 10. -7 mol / (m²·s·Pa), H2 / CO2 selectivity is 25 (800℃).
[0088] The liquid rejection rate of the obtained ceramic membrane was determined according to GB / T32360-2015 "Test Methods for Ultrafiltration Membranes". The results were: Potassium dichromate (Cr2O7) 2- Particle size: 0.48~0.78nm) with an interception rate greater than 96%.
[0089] The high-temperature stability of the obtained ceramic film was determined according to GB / T 37246-2018 "Test Method for Thermal Shock Resistance of Fine Ceramics". The results were: after oxidation at 1200℃ for 100 hours, the weight loss rate was <3.7%.
[0090] Example 2 Prolyl polysilazane was dissolved in acetone to form a 10 wt% solution containing propyl polysilazane. Other operations were the same as in Example 1.
[0091] The gas permeability of the obtained ceramic membrane was determined according to GB / T 1969-1996 "Test Method for Permeability of Porous Ceramics". The result was: He flux > 10. -6 mol / (m²·s·Pa), H2 / CO2 selectivity is 20 (800℃).
[0092] The liquid rejection rate of the obtained ceramic membrane was determined according to GB / T32360-2015 "Test Methods for Ultrafiltration Membranes". The results were: Potassium dichromate (Cr2O7) 2- Particle size: 0.48~0.78nm) with an interception rate greater than 93%.
[0093] The high-temperature stability of the obtained ceramic film was determined according to GB / T 37246-2018 "Test Method for Thermal Shock Resistance of Fine Ceramics". The results were: after oxidation at 1200℃ for 100 hours, the weight loss rate was <5%.
[0094] Example 3 The 30wt% solution containing propargyl polysilazane in Example 1 was replaced with Durazane 1500 rapid cure fast-drying resin, an organopolysilazane purchased from Merck, Germany. Other operations were the same as in Example 1.
[0095] The gas permeability of the obtained ceramic membrane was determined according to GB / T 1969-1996 "Test Method for Permeability of Porous Ceramics". The result was: He flux was 10. -7 mol / (m²·s·Pa), H2 / CO2 selectivity is 40 (800℃).
[0096] The liquid rejection rate of the obtained ceramic membrane was determined according to GB / T32360-2015 "Test Methods for Ultrafiltration Membranes". The results were: Potassium dichromate (Cr2O7) 2- Particle size: 0.48~0.78nm) with an interception rate greater than 99%.
[0097] The high-temperature stability of the obtained ceramic film was determined according to GB / T 37246-2018 "Test Method for Thermal Shock Resistance of Fine Ceramics". The results were: after oxidation at 1200℃ for 100 hours, the weight loss rate was <3.5%.
[0098] Comparative Example 1 In Example 1, propargyl polysilazane was replaced with domestically produced ordinary polysilazane resin (molecular weight 600-1000), and other operations were the same as in Example 1.
[0099] The gas permeability of the obtained ceramic membrane was determined according to GB / T 1969-1996 "Test Method for Permeability of Porous Ceramics". The result was: He flux was 10. -6 mol / (m²·s·Pa), H2 / CO2 selectivity is 25 (800℃).
[0100] The liquid rejection rate of the obtained ceramic membrane was determined according to GB / T32360-2015 "Test Methods for Ultrafiltration Membranes". The results were: Potassium dichromate (Cr2O7) 2- Particle size: 0.48~0.78nm) with an interception rate greater than 92%.
[0101] The high-temperature stability of the obtained ceramic film was determined according to GB / T 37246-2018 "Test Method for Thermal Shock Resistance of Fine Ceramics". The results were: after oxidation at 1200℃ for 100 hours, the weight loss rate was <4.5%.
[0102] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a recrystallized silicon carbide-silicon carbonitride ceramic film, comprising the following steps: After the first application of a polysilazane solution onto a porous matrix, a first pyrolysis is performed to obtain a pyrolytic material. A second pyrolysis was performed after a second application of a polysilazane solution onto the pyrolysis material to obtain the recrystallized silicon carbide-silicon carbonitride ceramic film. The first pyrolysis process is as follows: The temperature was increased from room temperature to 300℃ at a rate of 1~2℃ / min for the first heat preservation. The temperature is increased from 300℃ to 600℃ at a rate of 2~5℃ / min for the second heat preservation. The temperature is increased from 600℃ to 1000℃ at a rate of 3~5℃ / min for the third heat preservation. The temperature was increased from 1000℃ to 1200℃ at a rate of 2℃ / min for the fourth heat preservation. Repeat the process of first pyrolysis after first applying polysilazane solution to the porous matrix until the pore size of the pyrolysis material is less than or equal to 1 nm. The second pyrolysis includes sequentially performing a first pyrolysis and recrystallization; The recrystallization process is as follows: The temperature was increased from 1200℃ to 1400℃ at a rate of 2℃ / min for the fifth heat preservation. The temperature was increased from 1400℃ to 1600℃ at a rate of 2~5℃ / min for the sixth heat preservation. The recrystallization is carried out under a nitrogen atmosphere or an ammonia atmosphere; The polysilazane solution is a solution containing propargyl polysilazane or an organopolysilazane Durrazane 1500 RapidCure fast-drying resin. The propargyl polysilazane contains 10-30 mol of propargyl groups.
2. The preparation method according to claim 1, characterized in that, The first heat preservation time is 1-2 hours, the second heat preservation time is 2 hours, the third heat preservation time is 2 hours, the fourth heat preservation time is 1-2 hours, the fifth heat preservation time is 1 hour, and the sixth heat preservation time is 2 hours.
3. The preparation method according to claim 1, characterized in that, The preparation method of the propargyl polysilazane includes the following steps: The polysilazane oligomer, triethylamine, and toluene were mixed, and bromopropyne was added dropwise to the resulting mixture to carry out a condensation reaction, thereby obtaining the propyne-based polysilazane.
4. The preparation method according to claim 3, characterized in that, The average molecular weight of the polysilazane oligomer is 900-1000, the molar ratio of the polysilazane oligomer to triethylamine is 3:0.8-1.2, and the molar ratio of the polysilazane oligomer to bromopropyne is 9:0.8-1.2; the condensation reaction is carried out at a temperature of 60°C for 5 hours.
5. The preparation method according to claim 1, 3, or 4, characterized in that, The concentration of the solution containing propargyl polysilazane is 10-30 wt%, and the solvent includes one or more of ethyl acetate, toluene, and acetone. The first and second applications are performed by immersion lifting; the immersion lifting speed is 0.1~10mm / s.
6. The preparation method according to claim 1, characterized in that, The porous substrate includes a support and a microfiltration membrane and an ultrafiltration membrane sequentially located on the support; the microfiltration membrane has a pore size of 0.5~1μm and a thickness of 40~60μm; the ultrafiltration membrane has a pore size of 20~50nm and a thickness of 30~50μm.
7. The preparation method according to claim 1 or 6, characterized in that, The method for preparing the porous matrix includes the following steps: Silicon carbide, cellulose, dextran, vegetable oil, water and glycerol are mixed and then kneaded, extruded, degummed and sintered in sequence to obtain a support. A microfiltration coating is applied to the support, and a second sintering is performed to obtain a microfiltration body with a support-microfiltration membrane. An ultrafiltration coating is applied to the microfiltration membrane of the microfiltration body, and a third sintering is performed to obtain the porous matrix.
8. The preparation method according to claim 7, characterized in that, The support material consists of silicon carbide, cellulose, dextran, vegetable oil, water, and glycerol; the mass percentage of each component in the support material is 70% silicon carbide, 6% cellulose, 3% dextran, 1% vegetable oil, 19% water, and 1% glycerol. The kneading time is 3-5 hours; the degumming temperature is 140-160℃ and the time is 8-12 hours. The first sintering process is as follows: The temperature is increased from room temperature by 1-2℃ to 590-610℃ and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1.5~2.5 hours. The temperature is increased from 2190~2210℃ to 2440~2460℃ at a rate of 3~5℃ / min and held for 1~3 hours. After the first sintering, the process further includes cooling to room temperature, wherein the cooling rate is 2~5℃ / min.
9. The preparation method according to claim 7, characterized in that, The microfiltration coating comprises the following components by weight percentage: The composition includes 60% silicon carbide powder, 10% vegetable oil, 25% water, and 5% glycerol; the particle size of the silicon carbide powder is 7 μm. The second sintering process is as follows: The temperature is increased from room temperature to 590-610℃ at a rate of 1-2℃ / min and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 1~3 hours. After the second sintering, the process further includes cooling to room temperature at a rate of 2-5°C / min.
10. The preparation method according to claim 7, characterized in that, The ultrafiltration coating comprises the following components by mass percentage: The composition includes 60% silicon carbide powder, 10% vegetable oil, 25% water, and 5% glycerol; the particle size of the silicon carbide powder is 0.5 μm. The third sintering process is as follows: The temperature is increased from room temperature to 590-610℃ at a rate of 1-2℃ / min and held for 0.5-1.5 hours. The temperature is increased from 590~610℃ to 1590~1610℃ at a rate of 5~10℃ / min and held for 0.5~1.5h. The temperature is increased from 1590~1610℃ to 2190~2210℃ at a rate of 3~5℃ / min and held for 0.5~1.5h. After the third sintering, the process further includes cooling to room temperature at a rate of 2-5°C / min.
Citation Information
Patent Citations
Novel composite ceramic coating for preventing carburization of ethylene cracking tube and preparation method thereof
CN117721448A
Preparation method of high-purity silicon carbide product
CN119954516A
Additive Manufacturing of Polymer Derived Ceramics
US20170233300A1
Cited By
Porous recrystallized silicon carbide-based catalytic module as well as preparation method and application thereof
CN121534753A
A porous recrystallized silicon carbide-based catalytic module and a preparation method and application thereof
CN121534753B